Identify Positive Dominant Factors of Employee Loyalty On Generation X and Millennial: Case Study of State-Owned Enterprise In Bandung - Nanda Putri, Assyifa Fauziah; Pritasari, Adita (Journal of Business and Management, 2019)
The recent condition for workforce in most of companies today were dominated by two generations which are Generation X and Millennial. Researcher interested to learn the difference factors that influenced loyalty of employees because employee loyalty played an important role for the continuity of a company to adjust to changes. State-Owned Enterprise or BUMN (Badan Usaha Milik Negara) has a vital role for the economy and national income of the country. In the face of the industrial era 4.0, the State-Owned Enterprise is currently encouraged to make transformation in the field of human resource by starting to attract Millennial to enter SOE companies. This condition leads to retirement of baby boomers, Generation X replaced them and started to move into management positions, and Millennial are starting to get into the workforce and increase rapidly in the organization. Bandung has a high population of Millennial who are aged 20-38 by 900,833 people and for Generation X who are aged 39-53 are 684,460 people. Therefore, SOE companies especially in Bandung need to understand the difference for each generation that dominated the workforce to maintain their loyalty. Objective of the study is to find out the factors that are the most influencing drivers for each Generation X and Millennial which has known as the dominated generation in the workforce. This research is based on several theories of employee loyalty factor for general, and also specifically generation X and Millennial. By using quantitative method, researcher distributed the questionnaire in 4 SOE companies in Bandung and analyzed using multiple regression method. The result of this study indicated that there are different dominant factors affecting employee loyalty, the Flexibility for Generation X and Skill Development for Millennial.